Impact of Post-Primary Treatment Hormone Replacement Therapy on Survival in Women with Cervical Cancer - Hee Joong Lee; Banghyun Lee (Cancers, 2026)
Background/Objectives: The effects of hormone replacement therapy (HRT) after primary treatment on survival outcomes in women with cervical cancer (CC) remain unclear. This nationwide cohort study evaluated the association between post-primary treatment HRT and overall survival (OS) in women with CC. Methods: We identified 15,261 women aged ≤60 years with CC who received primary treatment using the Korean Health Insurance Review and Assessment Service database. HRT users were defined as women who received HRT prescriptions for ≥28 days within one year after completion of primary treatment. Stabilized inverse probability of treatment weighting (IPTW) was used to reduce baseline differences between HRT users and non-users, followed by multivariable Cox regression to further adjust for potential confounding. Landmark analyses were performed to address potential immortal time bias. Results: Among 15,261 women, 4118 (27.0%) received HRT. In IPTW-weighted analyses, HRT use was significantly associated with improved OS in both multivariable models (adjusted HR, 0.544; 95% CI, 0.502–0.590; p < 0.001 and adjusted HR, 0.653; 95% CI, 0.574–0.742; p < 0.001, respectively). This association was generally maintained in landmark analyses at 1, 3, and 5 years after diagnosis and remained significant across localized, regional, and distant disease in stage-stratified analyses. The association was most consistently observed among women with squamous cell carcinoma. Conclusions: Post-primary treatment HRT was associated with improved OS in women with CC. Further prospective studies are needed to clarify the clinical implications of this association.